Clinical and Microbiological Comparison of Acanthamoeba Keratitis According to the Existence of Hypopyon - Yang Kyung Cho; Dae Won Kim (Cornea, 2026)
Purpose: To compare the clinical outcomes of patients with Acanthamoeba keratitis (AK) according to the existence of hypopyon. Methods: A retrospective analysis of microbiologically confirmed AK cases over the past 15 years was conducted. Nine eyes with hypopyon (group 1) and 29 eyes without hypopyon (group 2) were analyzed to study the differences in these 2 groups of AK eyes. The cases were diagnosed using conventional microscopic analysis with staining techniques with smear and cultural methods and were treated according to diagnosis. Results: There was no difference in the demographic profiles and duration of symptoms before first visit in the 2 groups. The presenting corneal features, presenting best-corrected visual acuity, and final best-corrected visual acuity were significantly different between groups ( P = 0.042, P = 0.002, P = 0.001, respectively). There were significant differences between groups in microbiologic diagnosis ( P < 0.001): bacteria with Acanthamoeba (0/9 in group 1 vs. 4/29 in group 2), fungus with Acanthamoeba (7/9 in group 1 vs. 0/29 in group 2), and Acanthamoeba only (2/9 in group 1 vs. 25/29 in group 2). The eyes with fungus and AK coinfection showed worse visual prognosis. Conclusions: AK with hypopyon can be a representative sign of fungal coinfection, which has a trend of a worse visual prognosis. It should immediately alert clinicians to initiate early antifungals and antiamoebics.